METODE PEKERJAAN STRUKTUR LINING PADA PROYEK MODERNISASI IRIGASI RENTANG - Sobarna, Deli (Universitas Majalengka, 2022)
The Rentang Irrigation Area is a National strategic project located in the lowlands of the lower reaches of the Cimanuk River in the Northeastern part of West Java Province. Modernization of Irrigation is carried out because the age of the irrigation system is decades old, causing the performance of water services to decrease. meanwhile the objective of the Irrigation Modernization is the coating/installation of concrete block lining on river channels so as to reduce the water loss factor. Concrete block lining is a precast concrete specially designed for irrigation canals that function as retaining walls. There are 9 stages of work regarding the Concrete Block Lining Installation Implementation Method, starting from Preparation, Coffering, Dewatering, Cut And Fill, Subgrade, Concrete Block Lining, Caping Beam, Joint Sealent/Filler and Tool Shifting.